2016
DOI: 10.1007/s10143-016-0806-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes after minimally invasive transforaminal lumbar interbody fusion and lateral lumbar interbody fusion for treatment of degenerative lumbar disease: a systematic review and meta-analysis

Abstract: The surgical procedures used for arthrodesis in the lumbar spine for degenerative lumbar diseases remain controversial. This systematic review aims to assess and compare clinical outcomes along with the complications and fusion of each technique (minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) or minimally invasive lateral lumbar interbody fusion (MIS LLIF)) for treatment of degenerative lumbar diseases. Relevant studies were identified from Medline and Scopus from inception to July 19, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 103 publications
2
37
0
Order By: Relevance
“…One meta-analysis compared minimally invasive TLIF with LLIF and found that there were no differences in fusion or complication rates. However, it did find that minimally invasive TLIF patients had better Oswestry Disability Index (ODI) and visual analog scale (VAS) pain scores when compared with LLIF patients [28].…”
Section: Resultsmentioning
confidence: 99%
“…One meta-analysis compared minimally invasive TLIF with LLIF and found that there were no differences in fusion or complication rates. However, it did find that minimally invasive TLIF patients had better Oswestry Disability Index (ODI) and visual analog scale (VAS) pain scores when compared with LLIF patients [28].…”
Section: Resultsmentioning
confidence: 99%
“…Recent literature review weighted average mean of preoperative visual analogue scale (VAS) pain scores of 6.8, compared to a postoperative VAS score of 2.9 (p<0.0001) [ 25 ]. Neurological outcome in 91.7% of patients who were unchanged or improved following surgery was good compared to reported data[ 2,6,12,44 ]. 35 patients (48.6%) underwent previous surgery in the segment that underwent XLIF.…”
Section: Discussionmentioning
confidence: 98%
“…(30 patients), Paterakis et al [ 7 ](12 patients), Timothy et al [ 1 ] (14 patients), Attenello et al [ 49 ](22 patients), Tamburelli et al [ 27 ] (21 patients), Campbell et al [ 12 ](18 patients), Tessitore et al [ 50 ](20 patients), Blizzard et al [ 29 ] (11 patients), Lykissas et al [ 35 ](451 patient), Isaacs et al [ 51 ] (29 patients with XLIF). In lumbar interbody fusion, MIS-TLIF (minimally invasive transforaminal interbody fusion) had better ODI, VAS pain, and complication rate when compared to XLIF with direct and indirect meta-analysis methods;however, in terms of fusion rates, there were no differences between the two techniques[ 44 ].Radiological outcome showed similar results in patients with degenerative spinal canal stenosis and spondylodiscitis. Improvement of regional lordosis (increase of sagittal L1-S1 angle of 36.2⁰ preoperative vs. 38.09⁰ postoperative) showed consistence with previous studies[ 7,25,29,30 ].…”
mentioning
confidence: 96%
“…5,6 Minimally invasive lateral lumbar interbody fusion (LLIF) is now considered to be a standard approach for degenerative lumbar disorders. [24][25][26] Nevertheless, LLIF has some limits that need to be disclosed: neuromoni- toring is strictly needed due to the nonnegligible risk for nerve root injuries; the procedure cannot be performed at L5-S1 due to the iliac crest projection; and it is burdened by an intrinsic morbidity because of the violation of the psoas muscle. The necessity for aborting this procedure during the psoas transgression, especially for a highly degenerated and rotated L4-5 segment, is also a commonly reported experience.…”
Section: Discussionmentioning
confidence: 99%